INTELLECTUAL CAPITAL, FINANCIAL PERFORMANCE, AND VALUE OF COMPANIES REGISTERED IN JAKARTA ISLAMIC INDEX: SEM-PLS APPROACH - Ira Ragelia; Puji Sucia Sukmaningrum (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This study aims to analyze the effect of intellectual capital on firm value through financial performance as a intervening variable on companies that are consistently listed on the Jakarta Islamic Index from 2014 to 2018. Based on purposive sampling techniques, there are 15 companies used as research samples. This research tested used the Structural Equation Modeling method with Partial Least Square (SEM-PLS). The measurement of intellectual capital in this study uses the VAICTM method, which consists of Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), and Structural Capital Value Added (STVA). It was found that intellectual capital influence on firm's value directly and indirectly. Financial performance as a partial intermediary reflected through Return on Assets (ROA), Current Ratio (CR), Debt to Total Assets Ratio (DAR), Total Assets Turnover (TATO), and Earnings per Share (EPS). However, only ROA and TATO indicators can reflect financial performance variables. In the intellectual capital variable, there is only one valid indicator, namely physical and financial capital (VACA). The company's value in this study reflected through Market to Book Value and Tobin's Q.Keywords: intellectual capital, financial performance, firm’s value, SEM-PLS, Jakarta Islamic Index